RESEARCH ON THE PHYSICO-MECHANICAL PROPERTIES OF CAMOUFLAGE FABRICS USED IN CLOTHING AND INTERIOR DESIGN - RASTORHUIEVA, MARIIA; YEVTUSHENKO, VALENTYNA; OLIJNYK, HALINA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the physical and mechanical properties of camouflage fabrics and their role in modern clothing and interior design. Camouflage materials, traditionally used in the military sector, are gaining popularity in civilian consumption due to the combination of functionality, strength and aesthetic appeal. The influence of fabric structure on their mechanical strength, flexibility, wear resistance and resistance to external factors, including friction, moisture and ultraviolet radiation, was studied.  The study was conducted on seven samples of camouflage fabrics of different raw material composition, among which the most suitable for use in intensive operation were identified. It was found that sample No. 3 has the highest indicators of strength and wear resistance, and sample No. 7 demonstrates optimal elasticity and comfort. Assessment of color fastness showed that most fabrics have high indicators of resistance to washing, friction and chemical influences, which ensures their durability.  In addition to functional characteristics, camouflage fabrics play an important role in shaping modern fashion trends. They are actively used in the design of everyday and sportswear, accessories and interiors. Thanks to the development of textile production technologies, camouflage materials have acquired new properties, such as water repellency, thermoregulation and antimicrobial characteristics. This significantly expands the possibilities of their application and promotes integration into various industries.  Prospects for further research include improving dyeing technologies to increase color fastness, developing new textile materials with adaptive properties and introducing environmentally friendly production technologies. It is also important to analyze the impact of environmental factors on the operational characteristics of materials and find sustainable solutions for their secondary use.  The results obtained emphasize the prospects of camouflage fabrics not only for military purposes, but also for fashion clothing and interior textiles. In the modern world of light industry, their properties and functionality play a key role, determining the directions of future developments and the possibility of implementing innovative solutions.
Keywords: camouflage fabrics; physical and mechanical properties; interior; clothing; sustainability; structure